FGD PET/CT IN SUSPECTED RECURRENT CERVICAL CANCER - Stojiljković, Milica (Medicinski podmladak, 2023)
Carcinoma of uterine cervix represents the fourth most common malignant tumour and the fourth leading cause mortality from cancer in females, and approximately every third woman with cervical carcinoma diagnosis will develop relapse. For follow up and suspicion of recurrence of cervical cancer, various imaging modalities such as CT, MRI and PET/CT can be used. However, role of PET/CT is constantly increasing in these patients and the latest National Comprehensive Cancer Network (NCCN) guideline Version 1.2023 recommends PET/CT as the imaging method of choice for follow-up of patients with disease stage II or higher, and for suspicion of recurrent or metastatic disease. PET/CT shows higher sensitivity and specificity than conventional imaging in suspected recurrent cervical cancer, particularly in evaluation of distant recurrent sites. Additional benefit of PET/CT in these patients is its impact on treatment management in approximately half of the patients. PET/CT also has prognostic role in predicting progression free and overall survival, with patients with positive PET/CT for recurrence showing significantly worse prognosis.